A one-step laser process for rapid manufacture of mesoscopic perovskite solar cells prepared under high relative humidity. Issue 6 (11th April 2018) - Chen, Qian; Mokhtar, Muhamad Z.; Ke, Jack Chun-Ren; Thomas, Andrew G.; Hadi, Aseel; Whittaker, Eric; Curioni, Michele; Liu, Zhu
Abstract : A one-step laser process is applied to fabricate mesoporous and compact TiO2 films in 1 min for perovskite solar cells. Abstract : Mesoscopic perovskite solar cells (PSCs) containing a TiO2 mesoporous structure and a compact TiO2 film have reached the highest power conversion efficiency (PCE) and excellent stability among various PSC structures. However, conventional fabrication of the mesoscopic structure requires high-temperature heating processes that are considerably time-consuming. Current methods also make it difficult to fabricate integrated or multifunctional devices on the same substrate. Laser processing offers an opportunity to develop a rapid, localized and precise treatment without damaging the substrate or surrounding materials. Here, we demonstrate a rapid and localized one-step fiber laser process to generate both mesoporous and compact TiO2 films on tin-doped indium oxide (ITO) glass. The average PCE obtained for the PSCs by laser irradiation for 1 min, prepared under a high relative humidity of around 60% by a one-step deposition method, is equivalent to that by furnace treatment for 2 h. A fundamental understanding of the laser sintering mechanism using a fiber laser with a wavelength of 1070 nm has also been established. The use of the fiber laser with a wall-plug efficiency of over 40% offers an economically feasible, industrially viable solution to the challenge of rapid fabrication of mesoscopic PSCs and integration of multifunctional devices. In addition, it opens a novel route to manufacture tandem, patterned or aesthetic solar cells in the future.